Vêm de Belém e vêm da Grécia! Metamorfoses: fronteiras entre narrativas orais e os mitos - ALMEIDA, Natasha de Queiroz (Universidade Federal do Pará, 2014)
According to Jean Chavelier and Alan Gheerbrant, the metamorphoses is defined in this study as the physical and/or behavior transformation of a being to another, without the loss of identity and science of the first one. This transformation is a recursive phenomenon in many mythologies and cultures. This work aims to establish a comparative approach between correlations and differences among the recurrent theme of metamorphosis in Greek myths related by Homero, in his Odyssey, the Greek myths described by the Latin poet PubliusOvidiusNaso, known as Ovídio, in his work Metamorphoses, the first five books, and between the oral narratives that refer cases of metamorphosis occurred in the city of Belém do Pará, scheduled from 1994 to 2004. Odyssey and Metamorfoses were the considered ones because both, respectively, are exponents of western literature from Greece of VIII-VII centuries (b.C.) and the Greece of first century (a.C.) portrayed by the Latin poet Ovid, and they carry the theme of metamorphosis.This is why the previous study ratifies the formation of mythical indexes, not only in the narratives of Greek mythology but also in cases of metamorphoses from Belém. In both narratives is noted the space and temporal configuration as entities that consolidate and organize the mythical world, linking these two dimensions to representations in the physical and spiritual world. However, the metamorphose theme is shaped differently, according to the historical and cultural context of each narrative which is reflected in the variety of symbols and meanings persecuted for each narrative. In order to enrich the study of symbols and historical and geographical context of the Greek myths discussed before, the manuals of Junito Brandão are used as a complementary source, that is, the work Mythology by Junito Brandão, in Volumes I, II and III, as well as the two volumes of the Mythic-Etymological Dictionary of Greek Mythology. For a better comparative analysis, it was necessary to search beyond the study of contextual study of production and representation of the underlying codes in each narrative, in the Ernest Cassirer words, the myth is tried in consciousness, but is above it. The man lives the myth, so the myth comes before the man, since he realizes the conscience of his existence and the relations that weaves with the world. The man relies on the myth to establish relations of value and meaning, as well as representations to individualize his experiences. So, it is about a philosophical question of vital importance, that’s why to this literary, narrative and logical study was sought the fundamentals of the philosophy of mythology along with considerations of a cultural anthropology, connected to the contextual and historical survey of the cosmos that forms each narrative, in order to launch clarifier bases about the man relations with his world as from certain transformations. So, with this prior research on the narratives that will be analyzed, it was noticed that the metamorphoses had higher occurrences when: 1) Symbolized evil in the figure of metamorphosed ones; 2) Had motivations of sexual nature and 3) consisted in explanations for events in the physical and spiritual world. It’s about a methodological division that aims to enable the organization and visualization of the compared study. The conclusion, then, is that besides of enable the reading and the knowledge of Greek myths and the reports of Amazon by the symbols constituted in mythical consciousness, this study can serve as a basis for verification of literary exercise of creative language through the action of narrate, as well as magnify the understanding of what is and what makes human consciousness as support for the spread of behaviors and beliefs shared by the individual in society.